SIKAP SULTAN SYARIF KASIM II ABDUL JALIL SYAIFUDIN TERHADAP KEMERDEKAAN INDONESIA - Ricko Rahmad; Ridwan Melay; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The word Siak Sri Inderapura, literally can mean the city center of a religiously devout king, in Sanskrit, sri means "glowing" & senses or senses can mean king. While the temple can mean by "city" or "kingdom". Siak in the assumption that the Malay community is very closely tied to the religion of Islam, the Siak people are people who are experts in Islam, if someone lives diligently in religion it can be said to be the Siak People. The name Siak, can refer to a clan in the region between Pakistan & India, Sihag or Asiagh which means sword. This kingdom was founded in Buantan by the Little King of Pagaruyung, with the title Sultan Abdul Jalil in 1723, after previously being involved in the struggle for the throne of Johor. In its development, the Siak Sultanate emerged as a strong maritime kingdom & became a force calculated on the eastern coast of Sumatra & the Malay Peninsula.Keyword: Sultan Syarif Kasim II Abdul Jalil Syaifudin. Indonesia Independence